Menarche and pubertal progression: A cross-sectional analysis of timing and influencing factors in North-Eastern Ghana - Alatiah, Gabriel Ajediwe; Azupogo, Fusta; Atosona, Ambrose; Vuvor, Frederick; Steiner-Asiedu, Matilda; Brouwer, Inge D. (Cambridge University Press, 2025)
Menarche and pubertal onset vary across populations but understanding age-at-menarche (AAM) and pubertal growth tempo is limited in low-income settings. Identifying factors influencing pubertal development is vital for creating targeted health and education programmes supporting adolescent girls’ well-being. Baseline data (n = 1045) from the Ten2Twenty-Ghana study were analysed to examine menarche attainment, pubertal development, AAM, and the associated factors among girls aged 10-17 years in the Mion district, Ghana. The data collection methods included anthropometry, body composition, haemoglobin status, a qualitative 24-hour dietary recall, a food frequency questionnaire, and a pubertal development score (PDS). Binary logistic and linear regression analyses were used to model odds ratios for menarche attainment and regression coefficients for AAM and PDS. About 19.9% of the girls had experienced menarche, with a mean AAM of 13.4 ± 1.5 years. Among post-menarche girls (n = 205/1045), 12.2% and 15.1% experienced early (AAM < 12 years) and late menarche (AAM < 15 years), respectively. The mean PDS was 1.8 ± 0.7 out of 4. Among the adolescent girls, 36.2% were prepubertal, 17.0% early –pubertal, 18.6% mid-pubertal, 27.9% late pubertal, and less than 1% were in the post-pubertal stage. An increase in fat mass (FM), fat-free mass (FFM), height-for-age-z-score (HAZ), and body mass index-for-age-z-score (BAZ) was observed with puberty progression, but a steep decline in HAZ was noticed for girls in late puberty, increasing again post-puberty. Being older (adjusted odds ratio (AOR) = 2.06, 95% C.I.: 1.83, 2.31), stunted (AOR= 0.20, 95% C.I.: 0.10, 0.40), thin (AOR = 0.30, 95% C.I.: 0.11, 0.80), and overweight/obese (AOR = 7.29, 95% C.I.: 2.60, 20.43) were the significant predictors of menarche attainment. Being older (β = 0.39, P < 0.0001), stunted (β= -0.92, P = 0.01), thin (β = 1.25, P = 0.01), and having a literate mother (β = -0.72, P = 0.03) were significantly associated with AMM. A higher HAZ, FM, FFM, age, and Konkomba ethnicity were positively associated with higher PDS. This study highlights the complexity of factors influencing menarche and pubertal development. These insights are essential for developing targeted health and educational programmes that address nutritional and socio-demographic disparities to promote adolescent girls’ well-being and healthy pubertal development.